Glucose-6-phosphate dehydrogenase activity measured by spectrophotometry and associated genetic variants from the Oromiya zone, Ethiopia - Kießling, Nora; Brintrup, Joaquin; Zeynudin, Ahmed; Abduselam, Nuredin; Götz, Sylvia; Mack, Margith; Pritsch, Michael; Wieser, Andreas; Kohne, Elisabeth; Berens-Riha, Nicole (Malaria journal, 2018)
The study aimed to gain first data on the prevalence of G6PD enzyme deficiency measured by spectrophotometry and associated genetic variants in Jimma and surroundings, Ethiopia. The area is a Plasmodium vivax endemic region, but 8-aminoquinolines such as primaquine are not recommended as G6PD testing is not available. Healthy volunteers were recruited at Jimma University, Ethiopia. Enzyme activity was tested by spectrophotometry at the University of Ulm, Germany. A G6PD RDT (Binax NOW G6PD, Alere, USA) was additionally performed. The G6PD gene was analysed for polymorphisms in a sub-population. Tests for haemoglobinopathies and the presence of malaria parasites were conducted. No severe or moderate (cut-off 60%) G6PD deficiency was found in 206 volunteers. Median male activity was 6.1 U/g Hb. Eleven participants (5.4%) showed activities between 70 and 80%. No haemoglobinopathy was detected. None of the subjects showed asymptomatic parasitaemia. One G6PD-A+ variant (A376G) and one new non-synonymous mutation (G445A) were found. As the prevalence of G6PD deficiency seems low in this area, the use of 8-aminoquinolines should be encouraged. However, reliable G6PD testing methods have to be implemented and safe cut-off levels need to be defined.